Using python for analytical and numerical solving of ordinary differential equations : Using python for analytical and numerical solving of ordinary differential equations - Kamolova, N.D. (MODERN PROBLEMS AND PROSPECTS OF APPLIED MATHEMATICS, 2024)
Abstract. In this article we discussed how to use Python programming language for solving ordinary differential equations, and here also showed some exmaples.